Lake Chad Regional Economic Memorandum : Technical Paper 4. Infrastructure and Structural Change in the Lake Chad Region - Lebrand, Mathild (World Bank, Washington, DC, 2021)
This paper focuses on the impact of infrastructure on economic development for the countries around the Lake Chad area, an economically- and socially-integrated area in north-west Africa that has development potential, but which has been undermined by multiple and interrelated drivers of fragility, conflict, and violence. The Lake Chad region comprises a set of administrative areas across Cameroon, Chad, Niger, and Nigeria that surround Lake Chad, with an estimated 17 million to 19 million people, who are primarily involved in agriculture and fishing activities. The region has one of the largest concentrations of extreme poverty in Sub-Saharan Africa and the world and lags in human development outcomes and access to key public services. The paper analyzes the impact of infrastructure in Cameroon, Chad and Nigeria, from a national and regional perspective, and with a particular focus on the Lake Chad area. The paper is structured as follows. Section two presents the data. Section three presents the empirical strategy and results. Section four develops a spatial general-equilibrium model to produce counterfactuals for more regional integration. Section five concludes.